Impact of different pharmacotherapies on long-term outcomes in patients with electrical storm - Schupp, Tobias; Behnes, Michael; Ellguth, Dominik; Müller, Julian; Reiser, Linda; Kern-Bollow, Armin; Taton, Gabriel; Reichelt, Thomas; Engelke, Niko; Kim, Seung‑Hyun; Borggrefe, Martin; Akın, Ibrahim (Pharmacology, 2019)
Objective: The study sought to assess the long-term prognostic impact of different pharmacotherapies, including angiotensin-converting enzyme inhibitor-inhibitor/angiotensin receptor blocker (ACEi/ARB), statins, and amiodarone in patients with electrical storm (ES). Background: Data regarding the outcome of patients with ES is limited. Methods: Consecutive patients with ES from 2002 to 2016 were included. Patients on ACEi/ARB were compared to patients without ACEi/ARB, respectively, for statin and amiodarone therapy. The primary prognostic endpoint was all-cause mortality at 4 years. Secondary endpoints comprised ES recurrences, rehospitalization, and major adverse cardiac events (MACE) at 4 years. Kaplan-Meier survival curves and multivariable Cox regression analyses were applied. Results: A total of 84 consecutive patients surviving episodes of ES was included. Beta-blocker was given in 95%, ACEi/ARB in 80%, statin in 60%, and amiodarone in 54%. ACEi/ARB patients were associated with improved all-cause mortality at 4 years (mortality rate 34 vs. 65%, log rank p = 0.018; HR 0.428; 95% CI 0.208-0.881; p = 0.021), as well as improved freedom from MACE. In contrast, statin and amiodarone therapy had no impact on long-term outcomes in ES patients. Conclusion: ACEi/ARB therapy is associated with improved survival and MACE in patients with ES, whereas statins and amiodarone therapy had no impact on long-term prognostic endpoints.
Gesehen am 27.05.2019